(untitled) (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
NGO is a non-governmental and non-profit organization, organized on a local, national or international level. NGOs in various fields in no doubt has achieved tremendous success in Bangladesh that has assisted in meeting the ever-changing requirements and needs of the social system. Thus, through this, the design concept applied was context switching. Nevertheless, NGOs do face different problems and challenges in accomplishing their respective goals which differ from organization to organization and region to region. In this context, an attempt is made in this paper to discuss some of the common problems and challenges faced by the NGOs in Bangladesh.